2021
DOI: 10.1159/000518058
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Causal Relationship between Serum Thyroid-Stimulating Hormone and Osteoporotic Bone Fractures

Abstract: <b><i>Objective:</i></b> We aimed to validate the association of genome-wide association study (GWAS)-identified loci and polygenic risk score with serum thyroid-stimulating hormone (TSH) concentrations and the diagnosis of hypothyroidism. Then, the causal relationship between serum TSH and osteoporotic bone fracture risk was tested. <b><i>Methods:</i></b> A cross-sectional study was done among patients of European Caucasian ethnicity recruited in Tayside (Scotla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In recent years, numerous researchers have conducted studies focusing on targets for longevity and age-related diseases [40][41][42] . Previous studies have explored associations between thyroid hormone-related characteristics such as hyperthyroidism, TSH, and TSH receptors and bone density in relation to TDFDs and osteoporosis, but the results seem to be inconsistent [43][44][45][46] . The present study included five distinct clinical phenotypes of thyroid disorders (including hyperthyroidism, hypothyroidism, and nonfunctional thyroid disease) as well as three clinical phenotypes of osteoporosis (including osteoporosis and fracture), providing a more comprehensive investigation into the causal association between TDFDs and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous researchers have conducted studies focusing on targets for longevity and age-related diseases [40][41][42] . Previous studies have explored associations between thyroid hormone-related characteristics such as hyperthyroidism, TSH, and TSH receptors and bone density in relation to TDFDs and osteoporosis, but the results seem to be inconsistent [43][44][45][46] . The present study included five distinct clinical phenotypes of thyroid disorders (including hyperthyroidism, hypothyroidism, and nonfunctional thyroid disease) as well as three clinical phenotypes of osteoporosis (including osteoporosis and fracture), providing a more comprehensive investigation into the causal association between TDFDs and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In a one-sample Mendelian randomization study ( n = 5599), genetically raised serum TSH was causally associated with decreased risk of an osteoporotic fracture in men but not in women. 17 In subjects with normal TSH in a Danish register-based study, the risks of hip fractures and MOF were increased with each SD unit of TSH decrease. 18 In a pooled analysis of 13 prospective cohort studies, in adults with baseline TSH of 0.45–4.49 mIU/L, lower TSH levels as well as higher FT4 levels were associated with increased risk of hip fractures.…”
Section: Introductionmentioning
confidence: 98%
“…Also, multiple studies have demonstrated that even subtle variation in thyroid function within the reference range associates with an increased risk of cardiovascular diseases, fractures, dementia, depression, and even mortality (4,(6)(7)(8)(9)(10)(11)(12). Some of these associations were found to be causal based on Mendelian randomization studies (13)(14)(15)(16). Therefore, there is…”
mentioning
confidence: 99%